The category of verb tense in the Russian, Kazakh and English languages based on the formation of grammatical competence (Eurasian Journal of Philology Science and Education, 2023)
The article considers the category of verb tense in Russian, Kazakh languages from the point of view of the formation of linguistic competence, since the type-time correlation of the verb is one of the central sections of morphology, and forms the correct speech competence.  Despite numerous and diverse studies in the field of the category of aspect and lexical expression of action in time, which are central issues of aspectology, none of the points of view expressed is still generally accepted. The difference in the perception of the lexical expression of the category of tense, namely in verbs, creates certain difficulties in teaching students languages that are not native during the implementation of the trilingualism program, which leads to the need to revise the formation of language competence on the basis of one of the main languages. Changing the view of the traditional approach to the study of grammatical categories of the aspect and tense of verbs in Russian and Kazakh languages leads to the search for ways to form speech competencies in accordance with the requirements of time. Russian and Kazakh languages mistakes, difficulties and confusions in learning have formed the need to create sets of exercises, in accordance with the need to form strong skills and abilities of using the specific-temporal categories of the verb in Russian and Kazakh languages in order to form language competence. The authors came to the conclusion that the use of various techniques and sets of exercises effectively affects the formation of language competence during the educational process at the university.